Attitudes of Pre-Service Music Teachers towards Value Education in Turkey - Ozgur Egilmez; Hatice Onuray Egilmez; Doruk Engur (International Journal of Evaluation and Research in Education (IJERE), 2018)
In the music education curriculum, which is implemented from 2017-2018 academic year, the directive for teaching values was prepared for the first time. In this context, the research was conducted by comparing the attitudes of pre-service music teachers towards values education in terms of some variables, which will be included in the courses of value education according to the new music education curriculum. Data collected using the values education attitude scale were analysed using t-test, Kruskal-Wallis H test, and Spearman's correlation coefficient. Results showed that attitude scores did not change according to gender or level of parents’ education but had a significant difference according to the year students were in. Scale scores were not correlated with the amount of parents' income or students’ GPAs. This study is crucial as it tries to determine the attitudes of pre-service music teachers who are assigned as music teachers in a few years and will conduct music lessons according to the Ministry of National Education music curriculum. Moreover, it aims to shed light on the determination of targets for values education in the training of pre-service music teachers in the institutions that train music teachers with the help of the results that this study offers.